Research on the Development Trends of Synthetic Biology from an Industrial Perspective - Shi, Chongwei (International Journal of Social Sciences and Public Administration, 2024)
Synthetic biology, as an emerging interdisciplinary field, integrates technologies from biology, engineering, and computer science to drive transformative changes across various industries. This paper provides a systematic analysis of the fundamental concepts of synthetic biology and its application status in major industrial sectors such as pharmaceuticals, agriculture, food, environmental protection, and energy from an industrial perspective. By exploring the development trends, technological driving factors, and challenges and opportunities in the commercialization process, the paper reveals the potential and prospects of synthetic biology in driving industrial innovation and upgrading. The research indicates that despite challenges such as technological standardization, cost control, and regulatory and ethical issues, synthetic biology shows significant development opportunities in emerging markets and interdisciplinary collaboration. Finally, the paper proposes future research directions to promote the further application and commercialization of synthetic biology technologies.